Prolyl hydroxylase inhibition mitigates allograft injury during liver transplantation - Harnoß, Jonathan M.; Cai, Jun; Hinterkopf, Sascha; Radhakrishnan, Praveen; Schmitt, Annabelle; Dupovac, Mareen; Nees, Lisa Katharina; Strowitzki, Moritz; Taylor, Cormac T.; Schneider, Martin (Transplantation, 2022)
Background. - Ischemia and reperfusion injury (IRI) determines primary allograft function after liver transplantation (LT). Primary graft dysfunction (PGD) is associated with increased morbidity and impaired graft survival and can eventually progress to graft failure requiring retransplantation. Hypoxia-inducible transcription factor-prolyl hydroxylase containing enzymes (PHD1, PHD2, and PHD3) are molecular oxygen sensors, which control the adaptive hypoxia response through the hypoxia-inducible factor (HIF). In this study, we have investigated pharmacological activation of the HIF pathway through inhibition of PHDs as a strategy to reduce PGD after LT. - Methods. - Primary rat hepatocytes were isolated and the impact of the pan-PHD small-molecule inhibitor ethyl-3,4-dihydroxybenzoate (EDHB) on HIF-1 and its downstream target gene expression assessed. Subsequently, various rodent models of segmental warm liver ischemia and reperfusion and orthotopic LT were applied to study the impact of EDHB on normothermic or combined cold and warm liver IRI. Liver enzyme levels and histology were analyzed to quantify hepatic IRI. - Results. - In vitro, EDHB induced HIF-1 signaling and significantly upregulated its downstream target heme-oxygenase 1 in primary rat hepatocytes. In vivo, after establishment of the optimal EDHB pretreatment conditions in a murine IRI model, EDHB pretreatment significantly mitigated hepatic IRI after warm segmental liver ischemia and reperfusion and allograft injury after orthotopic LT in rats. Mechanistically, EDHB stabilized HIF-1 in the liver and subsequently increased hepatoprotective heme-oxygenase 1 levels, which correlated with reduced hepatic IRI in these models. - Conclusions. - This proof-of-concept study establishes a strong therapeutic rationale for targeting PHDs with small-molecule inhibitors to mitigate PGD after LT.
Gesehen am 19.12.2022